Optimal A* Path Planning with Ant Colony Optimization on Multi-Robot Task Allocation for Manufacturing Model - Rawinun Praserttaweelap; Somyot Kiatwanidvilai (My University, 2021)
This paper presents the optimal path planning by using A* with ant colony optimization based on the multi-robot systems. The purpose of this research is to design an appropriate path planning model for manufacturing. The safety path and the processing time are the priority of the manufacturing. The main contribution of this study is the A* for path planning with the ant colony optimization for the lowest risk of collision (RC) searching. The 5 robots condition is the best condition for the minimum RC and the minimum processing time. The simulation results represent the suitable path planning prediction model for manufacturing systems.
Keywords: Advanced Manufacturing and Logistics Optimization; Robotic Path Planning Algorithms; Optimization and Search Problems